(untitled) (Bangladesh Journal of Medical Science, 2025)
Background This article focuses on the importance of nurses’ work in the field of palliative care, emphasizing their role in providing comprehensive care and support to patients with incurable diseases. Purpose The researchers analyzed both international and local scientific articles over the past 15 years to assess the importance of nurses’ role in patient care in palliative medicine. Method and materials Then, in the period from September to November 2022, a crosssectional study was conducted.The aim of the study was to evaluate the activities of nurses in palliative care centers in Kazakhstan and determine the level of patient satisfaction with this care. Result To do this, 99 patients from three palliative care centers in Kazakhstan were interviewed.In the second stage, Pearson’s chi-squared (χ2) statistical method was used to analyze potential relationships between various variables and patient satisfaction levels in relation to the work of nurses in palliative care centers. The third stage included a binary logistic regression analysis to assess the impact of nurses’ behavior on patient satisfaction. The results of the statistical analysis indicate that the amount of information provided by nurses has an impact on the level of patient satisfaction with the quality of nurses’ work. This assistance includes an integrated approach, which includes both medical care and psychological, social and spiritual support, providing comprehensive care for the patient and his loved ones. Conclusion The results of this study can serve as a basis for strengthening the work of nurses, who are an integral element in the medical care system, playing a key role in supporting palliative patients at a difficult life stage. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 136-144